Upaya Optimalisasi Kinerja Terhadap Peran Rehabilitasi Bagi Anak-Anak Yang Bermasalah Terhadap Penyalahgunaan Narkotika Di Kab.Karawang - Akmal Baihaqi; Enjang Suherman (Jurnal Ekonomi dan Bisnis Digital, 2024)
The research results show that the existing rehabilitation program has Some support includes support from professional staff. However, there is Weaknesses include gaps in family involvement in the process Rehabilitation, social stigma that is still strong, and lack of programs Sustainable post-rehabilitation efforts to optimize program performance Rehabilitation includes increasing family involvement at every stage Rehabilitation, reducing stigma through community education, and development Sustainable post-rehabilitation program. The aim of this research is To find out the role of rehabilitation for children who have problems with The essence is narcotics, using descriptive qualitative methods That efforts to optimize rehabilitation performance can increase effectiveness Program to help children who have problems with the ecosystem Drugs in Karawang district.